Indoor vision based guidance system for autonomous drone and control application - Parinya Suwansrikham (2018)
© 2017 IEEE. Drone is not the only high-tech toy anymore. It has been using an onboard range of applications from civilian to military, including indoor and outdoor operations. Outdoor drone relies on GPS signal to locate its position. It is different from the indoor drone. In this paper, the indoor drone is a review in many aspects also it is current one of must interested topic for researchers who have the main area in autonomous robotic and aerial technology.